Education for UN Sustainable Development Goal 12: A Cross-Curricular Program for Secondary Level Students - Kiely, Lisa; Parajuly, Keshav; Green, James A.; Fitzpatrick, Colin (Frontiers in Sustainability, 2021)
Dealing with complex sustainability challenges requires an integrated approach to thinking and hence learning. Well-designed, integrated sustainability educational programs at the school level can have a significant positive impact on sensitizing students in this area. We present the case of a cross-curricular educational program designed and implemented at secondary level school with a focus on sustainability of material resources used in electronic products–a fast-growing sector with a significant environmental footprint. Over a 4-week period, teachers of five subjects (science, geography, business, technology and civic, social and political education) tailored their classes to focus on the topic of critical raw materials as it relates to these subjects. Examining a control group against the intervention group before and after the program, we use the New Ecological Paradigm (NEP) scale as a measure of students' environmental beliefs in order to find out the extent to which the program helped the cohort of students develop and retain such an ecological paradigm. Students' pro-NEP improved after the program, including on several facets, such as belief in limits to growth. Findings suggest that our cross-curricular approach was able to influence the young students' environmental orientation in a desirable direction.